2006
DOI: 10.1097/01.blo.0000214414.06464.00
|View full text |Cite
|
Sign up to set email alerts
|

Impaction Grafting for Bone Defects in Revision Total Knee Arthroplasty

Abstract: Therapeutic study, Level IV (case series).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
55
2
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(63 citation statements)
references
References 24 publications
0
55
2
6
Order By: Relevance
“…There was unquestionable radiographic incorporation in all except 2 in the tibia. Lotke et al (2006) reported favorable medium-term results in 48 consecutive cemented revision total knee arthroplasties with uncontained defects, and treated with IBG and additional steel mesh. He described no mechanical failures; there was incorporation and remodeling of all bone grafts, but there were 2 periprosthetic fractures related to poor host bone quality, 2 infections, and 2 patella clunk syndromes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was unquestionable radiographic incorporation in all except 2 in the tibia. Lotke et al (2006) reported favorable medium-term results in 48 consecutive cemented revision total knee arthroplasties with uncontained defects, and treated with IBG and additional steel mesh. He described no mechanical failures; there was incorporation and remodeling of all bone grafts, but there were 2 periprosthetic fractures related to poor host bone quality, 2 infections, and 2 patella clunk syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, although autogenous bone might be the best choice, large quantities of autograft of sufficient quality are often difficult to harvest-especially in elderly patients. In view of the good long-term results of IBG in revi-sion total hip arthroplasty (Schreurs et al 1998), we used IBG for biological reconstruction in knee revisions, which has shown promising results (Wilde et al 1990, Whiteside 1993, Ullmark and Hovelius 1996, Lotke et al 2006). Here we report the outcome of exchange arthroplasty with a hinge or rotational knee prosthesis combined with IBG.…”
mentioning
confidence: 99%
“…Two different techniques of applying these grafts have been described [5,20,[37][38][39][40]42], with impaction and without. Impaction grafting, which is widely used in revision hip surgery on the femoral and acetabular sides with good functional and radiographic results [3], also has been described in revision knee surgery with the use of cemented stemmed implants [5,20,42], with reported survivorship rates between 95% and 100% at short-term followup. Impaction grafting, however, requires a relatively large amount of bone graft, is expensive, time consuming, and technically challenging.…”
Section: Discussionmentioning
confidence: 99%
“…The use of morselized bone, although widely used in revision hip surgery [3], has not been commonly reported in revision TKA studies. Two different techniques are described in the literature (impacted [5,20,42] and loosely packed graft [37,40]). We have favored the use of loosely packed morselized bone to reconstitute bone loss when performing revision TKAs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation